Pengaruh Bulai pada Perubahan Indeks Kadar Klorofil, Serapan Fosforus dan Boron pada Jagung Manis - Achmad Azhari Sidik; Budi Nugroho; Untung Sudadi (Institut Pertanian Bogor, 2024)
Maize production and quality are affected by infection with plant pathogens. One of the maize's essential and main diseases is downy mildew caused by Peronosclerospora spp. Downy mildew is a limiting factor in increasing production and can reduce production by 80-100%. It is because the affected plant cannot produce cobs. Pathogens obtain nutrients from the host cell, which can kill the cell and damage the surrounding tissues, resulting in visible downy mildew symptoms. Boron (B) plays a role in forming phloem, increasing the fruit's number, weight, bunch weight, and diameter. The primary function of B at the molecular level is the cross-linking of pectin in the plant cell wall. Ramnogalacturonan II (RG II) is a pectic polysaccharide that contributes to the mechanical strength and properties of the primary wall cross-linked by borate diesters. Phosphorus (P) controls the downsides in the greenhouse and field conditions. This study aims to measure changes in chlorophyll index, P and B uptakes in downy mildew affected plants. The field experiment used a group randomized design with six natural phosphate (FA) application treatments and four groups of borax doses as replicates. The results showed that the downy mildew decreased the chlorophyll index of the leaves at different levels of attack. The results of P concentration according to the position of healthy plant leaves were significantly different due to P treatment. In contrast to concentration B, there is no real difference. P and B uptake results in downy mildew-infested plants showed a significant difference only in P uptake in leaves with 1 FA treatment. Keywords: boron, downy mildew, maize, phosphate